Early math skills in Chilean children with Developmental Language Disorder (DLD): Comparative study - Iturra-Osorio, Daniela; Espinoza Pastén, Laura; Vásquez, Fabián; Ygual Fernández, Amparo (Revista de Investigación en Logopedia, 2021)
In the last decades, there has been an increase in research on academic difficulties of children with Developmental Language Disorder (DLD). However, its relationship with mathematical skills has been less studied. The objective of this study was to determine whether there are relevant differences between the early mathematical abilities of children with DLD and those with typical development (TD). The sample included 78 children from 4 to 7 years 11 months old (44 children with DLD and 34 with TD) attending inclusive schools in Santiago, Chile. Comparisons of performance in mathematical tasks were established using the Spanish version of the Utrecht Early Mathematical Assessment Test (TEMT-U): relational subtest (comparison, classification, one-to-one correspondence and seriation), and numerical subtest (verbal count, structured counting, resultant counting, and general knowledge of numbers); finding a lower mathematical performance in the group with DLD of early childhood education in both subtest. The findings suggested that the difficulties inherent to children with DLD impact mathematical learning, especially in younger children, so it is imperative to reduce the barriers that hinder their learning process.